Integrating Material Circularity and Green Logistics Indicators in Supply Chain Performance Measurement Using the Green SCOR Model - Alina Cynthia Dewi; Maria Fiore Winni Kristianes; Mohammad Rachman Waluyo; Nurfajriah (Jurnal Manajemen Industri dan Logistik, 2026)
Integrating environmental considerations into supply chain performance measurement has become increasingly critical, growing sustainability and corporate responsibility. In the textile industry, particularly the non-woven sector, complex activities and mounting environmental pressures underscore the need for sustainability-oriented evaluation. The company lacks a supply chain performance measurement system that considers environmental aspects, creating a research gap that this study addresses. This study evaluates supply chain performance by embedding environmental dimensions into the measurement framework. The research was conducted in four stages: (1) identifying indicators through the Content Validity Index; (2) weighting indicators using the Analytic Hierarchy Process; (3) assessing performance with the Objective Matrix; and (4) classifying priorities through the Traffic Light System. A total of 22 validated indicators were applied, including three green indicators: Recycled Material Usage, Reusable Material, and Truck Load Optimization Rate. Recycled Material Usage was introduced as a novel indicator and validated as contextually significant for industrial supply chains. Results show a 2024 performance score of 5.678, classified as yellow under the Traffic Light System with five indicators as critical priorities for improvement. This study provides a regular monitoring tool that enables managers to establish a sustainable supply chain.